2000
DOI: 10.1002/1531-8249(200006)47:6<804::aid-ana14>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Progression in Parkinson's disease: A positron emission tomography study with a dopamine transporter ligand [18F]CFT

Abstract: We studied the rate of progression of striatal dopamine transporter function in Parkinson's disease (PD). Eight patients with early PD without antiparkinsonian medication and 7 healthy volunteers were investigated with [18F]CFT positron emission tomography (PET). The PET scan was carried out twice at an approximate 2‐year interval. The uptake of [18F]CFT was calculated as a region‐cerebellum:cerebellum ratio at 180 to 210 minutes after injection. At the first PET scan, the [18F]CFT uptake in PD patients in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
35
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(42 citation statements)
references
References 21 publications
7
35
0
Order By: Relevance
“…[14][15][16] UPDRS scores at baseline were considerably lower in SWEDD subjects compared with DAT deficit subjects, and there was no change in UPDRS scores during the 22-month follow-up in SWEDD subjects, compared with an increase in DAT deficit subjects consistent with other clinical studies of newly diagnosed PD. 2,[17][18][19] Subjects with a baseline SWEDD showed an equal sex distribution, rather than the expected male predominance in PD evident in most PD clinical studies.…”
Section: Resultssupporting
confidence: 87%
“…[14][15][16] UPDRS scores at baseline were considerably lower in SWEDD subjects compared with DAT deficit subjects, and there was no change in UPDRS scores during the 22-month follow-up in SWEDD subjects, compared with an increase in DAT deficit subjects consistent with other clinical studies of newly diagnosed PD. 2,[17][18][19] Subjects with a baseline SWEDD showed an equal sex distribution, rather than the expected male predominance in PD evident in most PD clinical studies.…”
Section: Resultssupporting
confidence: 87%
“…[47][48][49] In early PD patients treated with L-dopa putamen, 18 F-dopa uptake has been reported to decline annually by around 10% of baseline (5% of the normal mean), whereas caudate uptake falls at a slower rate. Similar rates of loss of putamen dopamine transporter binding have been reported with 18 F-CFT PET 50 and with 123 I-␤-CIT, 51 123 I-FP-CIT, 52 and 123 I-IPT SPECT. 53 …”
Section: Monitoring Pd Progressionsupporting
confidence: 77%
“…18 F]CFT as a radiotracer for the dopamine transporter, showed that the rate of annual decline in early PD patients, was 13,1% and 12,5% in the putamen and caudate nucleus, respectively (Nurmi et al, 2000). In addition, several [ 18 F]DOPA PET studies showed progression of disease in PD (Vingerhoets et al, 1994;Morrish et al, 1996Morrish et al, , 1998.…”
Section: Resultsmentioning
confidence: 99%